MELAS mutation in mtDNA binding site for transcription termination factor causes defects in protein synthesis and in respiration but no change in levels of upstream and downstream mature transcripts. - Chomyn, A (1992)
The pathogenetic mechanism of the mitochondrial tRNA(LeuUUR) gene mutation responsible for the MELAS (mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes) syndrome was investigated in transformants obtained by transfer of mitochondria from three genetically unrelated MELAS patients into human mitochondrial DNA (mtDNA)-less (rho 0) cells. Marked defects in mitochondrial protein synthesis and respiratory activity were observed in transformants containing virtually pure mutant mtDNA, as compared to the parent of the rho 0 cells (the 143B cell line) or to transformants containing exclusively wild-type mtDNA, derived from one of the patients or a maternally related asymptomatic individual. A striking protective effect against the mutation was exerted in the transformants by levels of residual wild-type mtDNA above 6%. The MELAS mutation occurs within the mtDNA binding site for a protein factor (mTERF) that promotes termination of transcription at the 16S rRNA/tRNA(LeuUUR) gene boundary. A marked decrease in affinity of purified mTERF for the mutant target sequence was observed in in vitro assays. By contrast, RNA transfer hybridization experiments failed to show any significant change in the steady-state amounts of the two rRNA species, encoded upstream of the termination site, and of the mRNAs encoded downstream, in the transformants carrying the MELAS mutation.